Respuesta :
Step-by-step explanation:
3a−2b=8
Add 2b to both sides.
3a=8+2b
The equation is in standard form.
3a=2b+8
Divide both sides by 3.
3
3a
=
3
2b+8
Dividing by 3 undoes the multiplication by 3.
a=
3
2b+8
3a−2b=8
Subtract 3a from both sides.
−2b=8−3a
Divide both sides by −2.
−2
−2b
=
−2
8−3a
Dividing by −2 undoes the multiplication by −2.
b=
−2
8−3a
Divide 8−3a by −2.
b=
2
3a
−4
Answer: a = 4, b = 2
Step-by-Step Explanation:
=> 3a - 2b = 8 (Eq. 1)
=> 2a - 2b = 4 (Eq. 2)
Subtracting Eq. 2 from 1, we get :-
a = 8 - 4
=> a = 4
Substitute value of ‘a’ in Eq. 1 :-
3a - 2b = 8
3(4) - 2b = 8
12 - 2b = 8
-2b = 8 - 12
-2b = -4
2b = 4
b = 4/2
=> b = 2
Therefore, a = 4 and b = 2
Step-by-Step Explanation:
=> 3a - 2b = 8 (Eq. 1)
=> 2a - 2b = 4 (Eq. 2)
Subtracting Eq. 2 from 1, we get :-
a = 8 - 4
=> a = 4
Substitute value of ‘a’ in Eq. 1 :-
3a - 2b = 8
3(4) - 2b = 8
12 - 2b = 8
-2b = 8 - 12
-2b = -4
2b = 4
b = 4/2
=> b = 2
Therefore, a = 4 and b = 2